7 - Navigating the Delicate Balance between Academia and Administration through Transformational Leadership in a South African University - Landa, Nhlanhla (Journal of Higher Education in Africa, 2022)
This study investigated the challenges faced by middle-level academic leaders at a university in South Africa. It was guided by the transformational leadership approach. The study found that heads of departments faced many challenges, including disruption of the teaching programme, due to meetings and other responsibilities as well as persistent student protests, too much paperwork as a result of reporting to higher management, and lack of leadership induction. The study also established that there was minimal academic career growth for academics in middle-level academic leadership during the time they were in those positions, due to the pressure that came with the office, which reduced research activities. There is a lack of support in terms of capacity-building for heads of departments, which functions as an impediment to career growth among middle-level academic leaders. Once they get into leadership positions, most academics sacrifice their academic careers to satisfy the administrative demands of their office. Balancing academia and administration at the sampled university was very difficult for the middle-level managers. The study recommends that the university develops and implements a practical strategy for middle-level academic managers, which would allow them to strike a balance between the administration and academic sides of their careers.